2010
DOI: 10.3892/ijo_00000795
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oncolytic reovirus against human gastric cancer with peritoneal metastasis in experimental animal model

Abstract: Abstract. The prognosis of gastric cancer patients with peritoneal dissemination is extremely poor, and the development of an effective treatment is necessary. The aim of this study was to investigate the efficacy of oncolytic reovirus against peritoneal metastasis in human gastric cancer using an experimental animal model. Four human gastric cancer cell lines, including MKN45p, NUGC4, MKN7 and KatoIII, a normal NIH3T3 cell line as a control, and reovirus serotype 3, were used in this study. We evaluated the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…However, H1437 cells were generated from a lung metastasis. Moreover, data from mouse models and clinical trials indicate that T3D (Reolysin) can target and kill metastases in mouse models and humans [22,38,39]. Thus, whether cell lines derive from primary versus metastatic tumors is unlikely to underlie strain-specific differences in cell killing.…”
Section: Discussionmentioning
confidence: 99%
“…However, H1437 cells were generated from a lung metastasis. Moreover, data from mouse models and clinical trials indicate that T3D (Reolysin) can target and kill metastases in mouse models and humans [22,38,39]. Thus, whether cell lines derive from primary versus metastatic tumors is unlikely to underlie strain-specific differences in cell killing.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, a study evaluating reovirus in Ras-activated gastric cancer models showed encouraging efficacy. 30 …”
Section: Upper Gastrointestinal Tract Malignanciesmentioning
confidence: 99%
“…Early preclinical studies with Reovirus demonstrated its ability to infect, replicate and induce cancer cell specific apoptosis with no activity in normal tissue across several gastrointestinal malignancies [18,19,20]. Reolysin (pelareorep) is a propriety formulation of the naturally occurring Reovirus Serotype3-Dearing strain, a live replication-competent Reovirus that has demonstrated cytotoxic effects on cancer cells that harbored mutations in the RAS signaling pathway with a tolerable safety profile [17,21,22,23,24].…”
Section: Reovirusmentioning
confidence: 99%